The Signaling Effect of Elite Connections: How Political-Military Networks Influence Financial Reporting Quality via Audit Mechanisms in Indonesia - Renna Magdalena; Oliandes Sondakh; Kathleen Feliciana Lantemona (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study examines how political and military connections among corporate elites influence financial reporting quality in Indonesian manufacturing companies during 2022–2024. The research also investigates the mediating role of the audit process in the relationship between board connections and financial reporting quality. Using secondary data from publicly listed firms, we analyze political and military affiliations of board members, audit delays, and Beneish M-Scores as proxies for financial reporting quality. The study adopts a signaling theory framework to explain how elite networks and audit mechanisms may interact within corporate governance. By focusing on Indonesian manufacturing companies, this research provides context-specific evidence relevant to emerging markets and contributes to the understanding of elite governance structures and their potential influence on reporting practices.